PENGARUH PENGETAHUAN SANITASI DAN HIGIENE TERHADAP PENGOLAHAN MAKANAN SEHAT KELUARGA LPKK - Chalin Mey Chatun; Sri Wahyu Andayani (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2015)
The objectives of this research are to know 1) the knowledge of sanitation and hygiene, 2) the process of health food for family, and 3) the influence of sanitation and hygiene to the process of health food for family. The type of the research is descriptive qualitative. Samples are taken by proportional random sampling technique. The method to collect the data is done by questionnaire and documentation. Validity and reliability are measured by instrument and the data is analyzed using product moment correlation.The result: the members of LPKK have knowledge about sanitation and hygiene in processing health food for family by fair category. Hypothesis measurement: 0,222 > 0,213. It means thatÂ  there isÂ  influence of sanitation and hygiene to the process of health food for family and the contribution given to the knowledge of sanitation and hygiene are 4.9%, and the other, 95.1% is influenced by other factor.Â